Caring for women with HIV/AIDS: an interactionist analysis from the perspective of female healthcare professionals - Tainara Serodio Amim Rangel Porto; Carla Marins Silva; Octavio Muniz da Costa Vargens
The aim of this study was to know the meanings attributed by female health professionals to the process of caring for women with HIV, considering their vulnerability in the context of feminization of HIV/AIDS. It is a qualitative study based on the grounded theory method and symbolic interactionism, conducted in two public maternity hospitals in Rio de Janeiro, from November 2009 to April 2010. Data were collected by means of semi-structured interviews with twelve female health professionals. The core category that emerged was "Speaking as a Professional and Thinking about Caring", which focused on the meaning of care, and the integration of two categories, the first being the concerns of being a woman/professional caring for women with HIV and the second being the meanings of professional care provided to women with the virus. It was concluded that the professionals still maintained the former perception of HIV/AIDS, contributing to increased gender vulnerability to HIV, discrimination and prejudice.